2017
DOI: 10.4253/wjge.v9.i5.211
|View full text |Cite
|
Sign up to set email alerts
|

Nerve preserving vs standard laparoscopic sacropexy: Postoperative bowel function

Abstract: AIMTo compare our developed nerve preserving technique with the non-nerve preserving one in terms of de novo bowel symptoms.METHODSPatients affected by symptomatic apical prolapse, admitted to our department and treated by nerve preserving laparoscopic sacropexy (LSP) between October, 2010 and April, 2013 (Group A or “interventional group”) were compared to those treated with the standard LSP, between September, 2007 and December, 2009 (Group B or “control group”). Functional and anatomical data were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In their review of the literature on sacrocolpopexy, functional outcomes and mesh placement, they concluded that the placement of the mesh posteriorly at the level of the levator ani muscle might be an explanation for the increased bowel dysfunction rate in those studies. That would support our data with low de novo bowel dysfunction as we place the mesh posteriorly at the level of the perineal body, according to Cosma et al . In our study, we observed a low de novo constipation rate of 5.3% and a significant decrease in the constipation rate of over 50% ( p < 0.004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In their review of the literature on sacrocolpopexy, functional outcomes and mesh placement, they concluded that the placement of the mesh posteriorly at the level of the levator ani muscle might be an explanation for the increased bowel dysfunction rate in those studies. That would support our data with low de novo bowel dysfunction as we place the mesh posteriorly at the level of the perineal body, according to Cosma et al . In our study, we observed a low de novo constipation rate of 5.3% and a significant decrease in the constipation rate of over 50% ( p < 0.004).…”
Section: Discussionsupporting
confidence: 91%
“…Cosma et al reported the only study regarding bowel function after NS‐SCP . Their small comparative study, with 25 women in the NS‐SCP group compared with 18 women in the standard sacrocolpopexy group, showed no de novo bowel dysfunction based on subjective outcome measures in the NS‐SCP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of 25 patients undergoing the NS technique was compared with a previous group of 18 patients undergoing the conventional technique to determine de novo bowel dysfunction postoperatively [10]. The NS group had no instances of bowel dysfunction as compared with 4 in the conventional group (p = .02).…”
Section: Urogynecologymentioning
confidence: 99%
“…However, eradication of the endometriosis, urogynecological reconstructive and oncological exenterative surgery, may require dissection planes far from the gynecological parametrial heart of the pelvis and a holistic, wider anatomical knowledge so as to decrease iatrogenic complications (Ceccaroni et al 2012 ; Cosma et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%